Challenges and Experience from UI GreenMetric’s 2nd International Virtual Event - Sari, Riri Fitri; Windiatmaja, Jauzak Hussaini; Ramadhianti, Sabrina Hikmah (Universitas Diponegoro, 2022)
UI GreenMetric World University Rankings is a non-profit initiative from Universitas Indonesia that ranks universities around the world based on their commitment and actions towards sustainability. During the ranking process, many universities’ performance in UI GreenMetric has progressed. To increase the performance of each university in UI GreenMetric, universities need to share their sustainability achievement and current condition in a forum. These universities can share information about the implementation of sustainability policies in each university through the International Workshop on UI GreenMetric World University Rankings. Due to the ongoing pandemic and our concerns that the event could ease the spread of coronavirus, this event was being held online. We evaluate the workshop to capture the experience gained in organizing the virtual event. From the topics modeling based on several regions, we conclude that university leaders around the world are very concerned about diverse sustainability issues, alongside the Covid-19 pandemic that has been going on for more than a year. We also conclude that people are getting more accustomed to virtual events, as evidenced by the increase in IWGM 2021 active participants of around 44% compared to 2020 virtual workshops. Keyword: green workshop, sustainability, digital transformation, online workshop, synchronous model, asynchronous model.